Race-Level Reporting of Incidents Using an Online System during Three Seasons (2019/2020–2021/2022) of Thoroughbred Flat Racing in New Zealand - Michaela J. Gibson; Kylie A. Legg; Erica K. Gee; Chris W. Rogers (Animals, 2022)
In the 2019/20 Thoroughbred racing season, the paper-based reporting process of stipendiary steward reports was upgraded to an online system (‘Infohorse database’) to allow for the rapid entry of precise event and injury data. The objectives of this study were to describe the incident and non-incident examinations during the 2019/20, 2020/21, and 2021/22 Thoroughbred flat racing seasons in New Zealand and describe the primary injury and reporting outcomes. The introduction of the online system was associated with fewer miscoding events with horse identification (0.1%). An improvement in the definition and prompts in reporting within the online system compared with the previous paper-based system resulted in a greater frequency of non-incident examinations being undertaken. The increased frequency of reporting the clinical outcome, ‘no observable abnormalities detected’ (NOAD), demonstrates the role of stipendiary stewards to carry out routine screening. The frequency of most clinical findings, such as musculoskeletal fractures (0.5 per 1000 starts, 95% CI = 0.3–0.6), remained similar compared to previously reported data using the paper-based system. The online system provided a more structured dataset compared with the paper-based system, making it a useful tool for the monitoring of incidents, injuries, and potential risk factors within Thoroughbred racing in New Zealand. Therefore, evidence-based changes to the management and structure of racing can be undertaken to ensure the industry meets its duty of care for racehorse and jockey welfare.